Efficacy of Ultrasound-Guided Erector Spinae Plane Block for Postoperative Analgesia in Modified Radical Mastectomy: A Prospective Comparative Interventional Study - Zainab Ali, Waseema Afzal, Fariha Aslam, Saba Arif, Zoia Khan, Syed Haider Mustafa Bukhari (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Modified radical mastectomy (MRM) is linked with significant postoperative pain, which can subsequently increase recovery period and increase opioid requirements. Ultrasound-guided erector spinae plane block (ESPB) has come up as as a novel regional anesthesia technique with potential analgesic effects. This study focused on evaluating the effectiveness of ESPB in reducing postsurgical pain and opioid utilization in patients treated with MRM. Material & Methods: This prospective comparative study included 60 female patients scheduled for elective MRM, who were allocated into two equal groups. Postoperative pain was assessed using the Visual Analogue Scale (VAS) at 4 hours. Rescue analgesic requirement was recorded in terms of tramadol consumption. Baseline demographic characteristics were compared using appropriate statistical tests. Subgroup analyses were performed according to age, weight, and ASA physical status. Results: Patients receiving ESPB had significantly lower VAS scores at 4 hours compared to the standard care group (1.57±0.77 vs. 4.53±0.97; p<0.001). Similarly, rescue tramadol consumption was significantly reduced in the ESPB group (2.77±0.97 mg vs. 10.63±2.27 mg; p<0.001). Subgroup analysis demonstrated consistent analgesic benefits of ESPB across age groups, body weight categories, and ASA physical status, with substantially lower pain scores and opioid need in all strata. Conclusion: Ultrasound-guided ESPB significantly reduces postsurgical pain intensity and opioid intake following modified radical mastectomy. Its analgesic efficacy remains consistent across different patient subgroups, supporting its role as an effective element of complex analgesia regime in breast surgery. Keywords: Erector spinae plane block; modified radical mastectomy; postoperative pain; tramadol; regional anesthesia; breast surgery.